Penerapan Design, Dynamics, Experience (DDE) Framework Pada Perancangan Gim Bermain Peran Karma - Darin Nadhifah; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Role playing is one type of video game that people are interested in. With the abundant story provided, players can interact more freely in playing this type of game. In the preparation of this game there are also many types of frameworks, depending on what the designer wants to achieve when the game is released and starts playing. One of the most well-known and most widely applied frameworks is Mechanic, Dynamic, Aesthetic (MDA). This framework can be used in all types of video games, so sometimes many aspects are missed in its design. Therefore, in this thesis project, the design of the role playing game uses a new framework that supports the designer to be able to exploit aspects of the experience of the players in the design of the role playing game. The karma role playing game is designed using the DDE (Design, Dynamic, Experience) framework and is implemented in the GameMakerLanguage language in the GameMaker Studio video game engine. The karma game is done using the Iterative and Rapid Prototyping process model. From the design process that enters the ‘Design' stage in DDE and trials to the tester enters the ‘Experience' stage. The 'Dynamic' stage exists to bridge the 'Design' stage and the 'Experience' stage. The results are obtained when the designer can meet the satisfaction of the testers.